Effect of COVID-19 lockdown on glycated haemoglobin testing and utilisation in KwaZulu-Natal, South Africa - Rucita Severaj; Verena Gounden (AOSIS, 2024)
Background: Diabetic monitoring and treatment guidelines are easily accessible, but compliance is poor in KwaZulu-Natal. The coronavirus disease 2019 (COVID-19) pandemic had a devastating impact on diabetic healthcare, both directly and through public health interventions. Objective: This study aimed to close the gaps in knowledge concerning glycated haemoglobin (HbA1c) test utilisation and how this was affected by the COVID-19 lockdown in KwaZulu-Natal. Methods: We reviewed HbA1c test volumes and results from public health facilities in the 11 health districts in KwaZulu-Natal, South Africa. We compared testing trends and glycaemic control between two 10-month study periods before (March 2019 - December 2019) and during (March 2020 - December 2020) the COVID-19 pandemic. Results: The number of HbA1c tests performed decreased 6.1% during the pandemic period, with 173 760 HbA1c tests performed in 2019 and 163 236 HbA1c tests performed in 2020. There was a statistically significant increase in the average HbA1c level during the pandemic (mean HbA1c level in the pre-pandemic period: 70.5 mmol/mol [8.6%] versus mean HbA1c level in the pandemic period: 72.7 mmol/mol [8.8%]; p-value 0.001). Of patients with suboptimal HbA1c results (83 421 in 2019, 83 259 in 2020), 11 656 (14.0%) in 2019 and 10 086 (12.1%) in 2020 had more than one HbA1c test performed during the study period. Conclusion: The COVID-19 pandemic impacted glycaemic monitoring in KwaZulu-Natal with lower HbA1c test volumes and worse glycaemic control seen during the pandemic. HbA1c testing practices are not in keeping with recommended guidelines. What this study adds: The study demonstrates that the COVID-19 pandemic impacted HbA1c utilisation in KwaZulu-Natal. Importantly, HbA1c testing practices in KwaZulu-Natal are not in keeping with Society for Endocrinology, Metabolism and Diabetes of South Africa guidelines regarding the monitoring of diabetic patients, and this requires more attention for future diabetic healthcare interventions.